ANALISIS LAYANAN STRATEGIC YANG MEMPENGARUHI SIKAP PENGGUNA SISTEM INFORMASI UNIVERITAS DEHASEN BENGKULU - Dwinda Etika Profesi; Kusrini Kusrini; M. Rudyanto Arief (Universitas Janabadra, 2018)
Information system is a system within an organization that brings together the needs of daily transaction processing, supports managerial operations, and strategic activities of an organization and provides certain outside parties with the necessary reports. One of them is Dehasen Bengkulu University that uses and utilizes information systems as a medium of information and to support academic activities. This study aims to conduct a behavior analysis of users of the Dehasen University information system in Bengkulu using the UTAUT method.This research was conducted using a quantitative method, with the population being students at Dehasen University in Bengkulu. The data analysis technique in this study used data normality test, multicollinearity test and Heteroscedacity test.From the results of the discussion after passing the data analysis test using the UTAUT method, it was found that the variable Performance Expectancy, Effort Expectancy had an effect on Behavior Intention and Facilitating Condition that affected the Use Behavior. Keywords: Dehasen University Bengkulu, Information System,Students, UTAUT